A Brief Review on Changes in Air Pollution Scenario over South Asia during COVID-19 Lockdown - Manisha Mishra; U. C. Kulshrestha (Aerosol and Air Quality Research)
Abstract In general, the lockdown to prevent the outbreak of COVID-19 pandemic has resulted in a better quality of air across the world. The concentrations of both particulate and majority of gaseous pollutants were decreased drastically due to total shutdown of outdoor activities in the initial phase. This has resulted in up to 50% reduction in the air quality index (AQI) over South Asian megacities. A significant reduction was observed over most polluted ranked cities in South Asia like Delhi (41%), Dhaka (16%), Kathmandu (32%), Colombo (33%) including Islamabad and Kabul. A major decrease was also observed in the gaseous pollutants like CO, NO2, and SO2. The strict lockdown provided an opportunity to the relevant authorities to reassess the large-scale transport and industrial sectors to avoid undue emissions of harmful pollutants. The present analysis suggests that there is a need of controlled emissions of air pollutants with reference to the lockdown values of ‘New Normal’, and to switch over to the cleaner fuel technology options at the earliest possible. There is a need to constitute an Inter-state agency to monitor trans-boundary and long-range transport of pollution across south Asia. Finally, a holistic approach for maintaining balance between ‘need and greed’ for energy and resource consumption is needed which can provide us the sustainable atmosphere and healthy air quality throughout the region.